APPLICATION OF GEOGRAPHIC INFORMATION SYSTEMS IN THE DETERMINATION OF POTENTIAL OF FISH IN THE WATERS ROKAN HILIR RIAU PROVINCE - Muhamar Ali; T. Ersti Yulika Sari; Usman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in October 2015 at the Indonesian Institute of Sciences. This research was conducted in two phases: the first phase is data collection in the field in October 2012, while the second stage is, data downloading and processing satellite image data Aqua MODIS conducted at the Laboratory of Remote Sensing Science Institute Indonesia North Jakarta Month October 2015 .the purpose of this study to present data information map of potential areas of fish in the territorial waters of RokanHilir And to see the changes from year to year in the same area. With the method of spatial analysis, field survey and GIS methods. Potential areas of fish are at 02° 24 'N - 100° 45' E, 02° 20'LU - 101° 19 'E, 02° 10' N - 101° 48 'E, 01° 49'LU - 102° 07' east longitudeKeyword :  GIS, Potential areas of fish, waters of RokanHilir